BRICS GROUP AS NEW FORMAT OF MULTIPOL AR FINANCIAL AND ECONOMIC ARCHITECTURE - I. I. Tumaikina (Финансы: теория и практика, 2017)
The modern world is characterized by multipolar development which important part is the prompt growth of the economies with emerging markets having more and more increasing impact on functioning of all spheres of global community. For the last some decades in world economy, there was a set of changes, which allowed the countries of BRICS group to take an important place on the world scene. This work is devoted to studying by studying of growth of influence of BRICS group on tendencies of development of world financial architecture. Relevance of this research is caused by rapid growth of the financial and economic capacity of member countries of BRICS group and the objective need for increase of their role for world monetary system connected with it in recent years. Brazil, Russia, India, China and the Republic of South Africa apply for a role of world leaders of the new millennium and seek to strengthen the influence on the processes happening on the international scene. The methods of the system analysis used in work, allowed to study in detail prerequisites of formation of BRICS group and growth of influence on development of world economy. The main achievements in development of cooperation of the countries of BRICS are analyzed and prospects for further interaction within BRICS group are defined. For strengthening of a role of BRICS group on the world scene, the tasks which decision will help the participating countries with formation of multipolar financial and economic architecture are set.